Social support in the workplace for physicians in specialization training. Issue 1 (1st January 2018) - Mikkola, Leena; Suutala, Elina; Parviainen, Heli
ABSTRACT: When becoming a specialist, learning-through-service plays a significant role. The workplace affords good opportunities for learning, but the service-learning period may also impose stress on phycisians in specialization training. In medical work, social support has proved to be a very important factor in managing stress. Social support may afford advantages also for learning and professional identity building. However, little was known about how social support is perceived by doctors in specialization training. This study aimed to understand the perceptions of physicians in specialization training regarding social support communication in their workplace during their learning-through-service period. The study was conducted qualitatively by inductively analyzing the physicians' descriptions of workplace communication. The dataset included 120 essays, 60 each from hospitals and primary healthcare centres. Physicians in specialization training explained the need of social support with the responsibilities and demands of their clinical work and the inability to control and manage their workloads. They perceived that social support works well for managing stress, but also for strengthening relational ties and one's professional identity. A leader's support was perceived as being effective, and both senior and junior colleagues were described as an important source of social support. Also co-workers, such as the individual nurse partner with whom one works, was mentioned as an important source of social support. The results of this study indicate that social support works at the relational and identity levels, which is due to the multi-functional nature of workplace communication. For example, consultation functions as situational problem-solving, but also the tone of social interaction is meaningful. Thus, strengthening one's professional identity or collegial relationships requires further attention to workplace communication. Abbreviations PiST: Physician in specialization training